Mulheres na ciência: uma avaliação das políticas públicas de apoio à maternidade implementadas no âmbito da pós-graduação da Universidade Federal do Ceará (UFC) - Rocha, Mírian Narjara Pires (2022)
The historical analysis of motherhood reveals this experience as a social construction (BEAUVOIR, 2019; BADINTER, 1985). Moreover, several interferences set up various forms of going through it, with emphasis to aspects such as race, ethnicity, and social class (AKOTIRENE, 2019; CRENSHAW, 1989; DAVIS, 1982; GONZALEZ, 2020; hooks, 2015). Feminist movements, especially starting from the second wave onwards, were essencial for problematizing motherhood and denying the inatism attributed to it. Women' status in society must consider the meanings attributed to motherhood, especially when it comes to the social pressure and the production of inequalities. Related to it, the sexual division of work, strictly related to the advent of capitalism (FEDERICI, 2004), produced severe disadvantages to women throughout the centuries, which until nowadays overload them. These problematics reverberate into scientific production and universities. The science field reproduces gender inequalities, hence collectives of Brazilian female scientists have been pressuring public authorities to implement public policies that support women who become mothers when they're still in the process of university graduation. However, the gained guarantees are still few when it comes to, as we call in this work, public policies in support of motherhood. Considering this scenario, this evaluative research is positioned in the field of public policies evaluation. The aim was to evaluate the public policies in support of motherhood, implemented within the scope of post-graduation at UFC, checking initiatives, structure and rights guaranteed or not by the institution and its unfolding in the journeys of post-graduate student mothers. In order to execute this study, the evaluative approach used was the In-Depth Examination, which presupposes the evaluation as production of knowledge. Besides, this approach enables an interdisciplinary and multidimensional character required in the evaluation of such policies (RODRIGUES, 2008, 2019; GUSSI, 2008, 2015, 2016 e 2019; GONÇALVES, 2008). In this type of evaluation, the understanding of the subjectivity of the subjects gains strength, and elements such as context and in process historicity are considered, which go beyond the purely technical dimension. From a methodological point of view, the research has a qualitative nature and included the development of documental and bibliographic analysis, plus in-depth interviews with 17 female students and alumni from eight post-graduation programs at UFC, among master's and doctoral degrees, aged between 26 to 39 years old, one black, one indigenous, seven brown and eight white. In addition, seven graduate coordinators, 3 women and 4 men, were interviewed, as well as a manager and a former manager of the Research and Postgraduate Dean's Office at UFC. It was noticed throughout the study, the need for improvements in existing policies, but mainly the lack of initiatives in the area of maternity support, both at local and federal levels. The main result of the work was a proposal with 18 qualitative indicators, divided into three spheres: economic, social and institutional. It is hoped, therefore, that improvements will be implemented in existing policies, that gaps will be filled and that the knowledge generated will collaborate with the confrontation against gender inequalities, at least in the academic environment.